Computational study on novel natural inhibitors targeting c-MET. Issue 38 (24th September 2021) - Hou, Yuanyuan; Xie, Haoqun; Dou, Gaojing; Yang, Wenzhuo; Ge, Junliang; Zhou, Baolin; Ren, Junan; Li, Juncheng; Wang, Jing; Zhang, Zhiyun; Wang, Xinhui
Abstract : Abstract: This study was designed to select ideal lead compounds and preclinical drug candidates http://dict.youdao.com/w/eng/preclinical_drug_candidate/javascript:void (0) ; with inhibitory effect on c-MET from the drug library (ZINC database). A battery of computer-aided virtual techniques was used to identify possible inhibitors of c-MET. A total of 17, 931 ligands were screened from the ZINC15 database. LibDock is applied for structure-based screening followed by absorption, distribution, metabolic, and excretion, and toxicity prediction. Molecular docking was conducted to confirm the binding affinity mechanism between the ligand and c-MET. Molecular dynamics simulations were used to assess the stability of ligand-c-MET complexes. Two new natural compounds ZINC000005879645 and ZINC000002528509 were found to bind to c-MET in the ZINC database, showing higher binding affinity. In addition, they were predicted to have lower rodent carcinogenicity, Ames mutagenicity, developmental toxicity potential, and high tolerance to cytochrome P4502D6. Molecular dynamics simulation shows that ZINC000005879645 and ZINC000002528509 have more favorable potential energies with c-MET, which could exist stably in the natural environment. This study suggests that ZINC000005879645 and ZINC000002528509 are ideal latent inhibitors of c-MET targeting. As drug candidates, these 2 compounds have low cytotoxicity and hepatotoxicity as well as important implications for the design and improvement of c-MET target drugs.